Predictors for mild parkinsonian signs: A prospective population-based study. Issue 3 (March 2015) - Mahlknecht, Philipp; Kiechl, Stefan; Stockner, Heike; Willeit, Johann; Gasperi, Arno; Poewe, Werner; Seppi, Klaus
Abstract: Objective: Mild parkinsonian signs (MPS) are common in the elderly population and are associated with a wide range of adverse health outcomes, including incident Parkinson's disease (PD). We aimed to prospectively evaluate potential risk factors for incident MPS. Methods: Participants of the population-based Bruneck Study representative for the general elderly community underwent a baseline assessment of substantia nigra (SN)-echogenicity with transcranial sonography, olfactory function with the Sniffin' Sticks identification test and vascular risk according to the Framingham risk score as well as a baseline and 5-year follow-up neurological examination. MPS were defined according to established criteria based on the entire motor section of the Unified PD Rating Scale. Participants with PD at baseline or follow-up and subjects with MPS at baseline were excluded. A logistic regression analysis adjusted for age and sex was used to detect risk factors for incident MPS in the remaining 393 participants. Results: SN-hyperechogenicity and hyposmia were related to the development of MPS with odds ratios of 2.0 (95%CI, 1.1–3.7) and 1.6 (95%CI, 1.0–2.7), respectively, while increased vascular risk was not. Having both, SN-hyperechogenicity and hyposmia, was associated with an odds ratio of 3.0 (95%CI, 1.2–7.7) for incident MPS. Among the various motor domains, increased SN-echogenicity predicted the development of bradykinesia and rigidity, whereas diminished olfactory function predicted the development of impaired axial motor function. Conclusions: In addition to their established roles as risk factors for PD, SN-hyperechogenicity and hyposmia are associated with an increased risk for MPS in the general elderly community. Highlights: We examined potential risk factors for the development of mild parkinsonian signs (MPS). We used the prospective population-based Bruneck Study cohort. Nigral hyperechogenicity and hyposmia were related to MPS risk. Nigrostriatal vulnerability contributes to the development of MPS in the elderly. Vascular risk may play a secondary role in the development of MPS.